IMPLEMENTATION OF BANDWIDTH MANAGEMENT IN MIKROTIK USING THE HIERARCHICAL TOKEN BUCKET AND QUEUE TREE METHOD - Shofa, Mohammad Arief (Jurnal Ilmu Teknik dan Komputer, 2025)
Computer network at the head office of PT. Indojaya Sukses Makmur uses Active Ethernet (AE) technology, which connects each point directly to the data center via active devices such as switches and routers. Employees often complain about slow web access due to excessive data usage and a large number of users, resulting in decreased network performance. Bandwidth management is a potential solution with fair bandwidth allocation and according to user needs. Previous research used simple queues, showing the advantages and disadvantages of each. Based on this research, this method has its own advantages and disadvantages. The simple queue method cannot use the entire bandwidth even though the bandwidth is available with the configuration carried out. Next, the focus of the research is the implementation of Quality of Service (QoS) with the title: "IMPLEMENTATION OF BANDWIDTH MANAGEMENT IN MIKROTIK USING THE HIERARCHICAL TOKEN BUCKET AND QUEUE TREE METHOD" to improve network efficiency and quality at PT. Indojaya Sukses Makmur.